Soil health and methods evaluation in producer’s fields of central Kansas - Petty, Adam (Kansas State University, 2023)
Soil health indicators are useful for evaluating dynamic soil properties, but there are concerns about their applicability across different regions spanning multiple management practices, soils, and climates. Cropland management practices have been shown to have measurable effects on dynamic soil properties, and many methods for measuring those properties have been, and are still being evaluated for their feasibility. This study assessed the efficacy of multiple methods measuring physical and biological dynamic soil properties in Central Kansas. In addition to evaluating the methods, this study examined the associations between various common management practices in this region and the differences between them in terms of these soil health indicators. The study was located in McPherson and Harvey counties of Kansas and included 100 pedons collected from producers’ fields. Pedons were sampled from 0-5, 5-10, 10 cm to the remainder of the A horizon, and by genetic horizon thereafter to a depth of 1 m. The fields chosen for sampling were part of a survey dating back to 2010 and as late as 2022 that monitored management practices every year. The primary variables of concern were cropping systems and irrigation. The four methods used to measure total aggregation were a multi-sieve machine method, a single-sieve hand method, the Cornell method, and a smartphone application called SLAKES. The fields sampled with the most tillage and least crop diversity, particularly continuous wheat, had the lowest total aggregation percentage (as defined by the smallest sieve used to retain macroaggregates within each method) and lowest mean weight diameter aggregates in the 0-5 cm and 5-10 cm depths compared to all other management systems. Among the four methods for measuring total aggregation there was moderate to strong correlation between all methods except the SLAKES method. SLAKES was weakly correlated to the machine method and the Cornell method and very weakly correlated to the hand method. The biological methods were phospholipid fatty acid analysis (PLFA), autoclaved citrate extractable protein (ACEP), and permanganate oxidizable carbon (POXC). Among these methods, POXC was the least sensitive and was the only method unable to detect differences in cropping systems at both 5-10 cm and 10 cm to the bottom of the A horizon (10 cm-x). PLFA total biomass was unable to detect differences between cropping systems at 10 cm-x, whereas ACEP was the only method to show significant differences between cropping systems at all three depths. Continuous wheat (which was conventionally tilled for the most part) resulted in many of the lowest values amongst the biological indicators as well, including POXC (0-5 cm), and all PLFA groups except for fungi (0-5 cm). Fungi significantly differentiated between perennial and all other systems. These results can help inform future management decisions for producers in this region of Kansas as well as inform researchers on the evaluated methods.
Keywords: Soil; Soil health